Pengaruh Interaksi Sosial dan Social Support terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Moderasi - Fauzia Afriyani; Marlina; John Sihar Manurung; Ikram Yakin; Rena Augia Putrie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze the influence of social interaction and social support on employee performance with job satisfaction as moderation. The analysis used in this research is a quantitative approach. The population of this study was employees from several companies totaling 65 people. The data collection techniques used in this research were questionnaires, interviews and literature studies, and the analysis method used Smart PLS software. The findings in this research are that social interaction and social support influence employee performance. Job satisfaction as a moderating variable is able to moderate social interaction and social support on employee performance.